Sinuolinea infections in the urinary system of Cynoscion species (Sciaenidae) and phylogenetic position of the type species of Sinuolinea Davis, 1917 (Myxozoa: Myxosporea) - Dyková, Iva; Kodádková, Alena; de Buron, Isaure; Fiala, Ivan; Roumillat, William A (International journal for parasitology. Parasites and wildlife, 2013)
Myxosporean infections that we diagnosed frequently in the urinary tract of Cynoscion nebulosus (Cuvier, 1830) and Cynoscion regalis (Bloch and Schneider, 1801) (Sciaenidae) collected in the estuarine systems of SC, USA, are described together with their etiological agent. Based on the morphology of spores and plasmodial stages, we identified the agent, in both fish host species, as Sinuolinea dimorpha (Davis, 1916), which is the type species of the genus. Based on sequences of SSU rDNA generated in this study from type host material, this species of SinuolineaDavis, 1917 has found its place in the current phylogenetic reconstruction of Myxozoa and enlarged the limited number of myxosporean genera represented in phylogenetic analyses by sequences of type species. Sequences of SSU rDNA of S. dimorpha from Cynoscion host species formed two clusters, irrespective of their host species, and also revealed differences within each cluster. These findings contribute to the acknowledgement of myxosporean cryptic species diversity, an important topic that emphasizes the general necessity of species delimitation and of continued effort to improve our knowledge of Myxosporea based on both morphology of spores and molecular data.